Observations of neutron radiation environment during Odyssey cruise to Mars. (May 2021) - Litvak, M.L.; Mitrofanov, I.G.; Sanin, A.B.; Bakhtin, B.; Golovin, D.V.; Zeitlin, C.
Highlights: HEND/Odyssey data were used to study the spacecraft neutron background. Neutron dose equivalent rate during mars odyssey cruise to mars was estimated. Cruise observations have been extrapolated to the different periods of solar cycle. Abstract: In April 2001, Mars Odyssey spacecraft with the High Energy Neutron Detector (HEND) onboard was launched to Mars. HEND/Odyssey was switched on measurement mode for most of transit to Mars to monitor variations of spacecraft background and solar activity. Although HEND/Odyssey was originally designed to measure Martian neutron albedo and to search for Martian subsurface water/water ice, its measurements during cruise phase to Mars are applicable to evaluate spacecraft ambient radiation background. The biological impact of the neutron component of this radiation background should be understood, as it must be taken into account in planning future human missions to Mars. We have modeled the spacecraft neutron spectral density and compared it with HEND measurements to estimate neutron dose equivalent rates during Odyssey cruise phase, which occurred during the maximum period of solar cycle 23. We find that the Odyssey ambient neutron environment during May – September 2001 yields 10.6 ± 2.0 μSv per day in the energy range from 0 to 15 MeV, and about 29 μSv per day when extrapolated to the 0–1000 MeV energy range during solar quiet time (intervals without Solar Particle Events, SPEs). We have also extrapolated HEND/Odyssey measurements to different periods of solar cycle and find that during solar minimum (maximum of GCR flux), the neutron dose equivalent rate during cruise to Mars could be as high as 52 μSv per day with the same shielding. These values are in good agreement with results reported for a similar measurement made with an instrument aboard the Mars Science Laboratory during its cruise to Mars in 2011–2012.